Kombinasi Multi Factor Evalution Process (MFEP) Dan Equal Weight Dalam Penentuan Tingkat Kesejahteraan Masyarakat - Sudipa, I Gede Iwan; Aryati, Komang Sri (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Community welfare reflects the equal distribution of social life in society. Various government assistance is provided to support the process of equal distribution of welfare. By knowing each community's level of welfare, aid can be provided on the right target principle. There are 21 assessment indicators used in determining the level of community welfare. In determining the level of community welfare, it is necessary to apply multicriteria decision-making techniques to determine the grouping of each category of community level. This study used a combination of the Multi-Factor Evaluation Process (MFEP) method to calculate the final evaluation value of 21 assessment indicators and determine the level of community welfare categories. Equal Weight method for determining the weight according to the number of assessment criteria with the same criterium importance. Combining the two methods above is to produce an alternative evaluation value and a category of community welfare level based on the final value of each alternative to the assessment indicator.